Gynecological Lymphoma: A Case Series and Review of the Literature. Issue 3 (May 2018) - Slonimsky, Einat; Korach, Jacob; Perri, Tamar; Davidson, Tima; Apter, Sara; Inbar, Yael
Abstract : Objective: The aim of the study was to evaluate the radiological characteristics of gynecological lymphoproliferative disease (LPD) and specific imaging features that may suggest the diagnosis. Methods: Two readers conducted a retrospective evaluation of imaging studies of 13 female patients presenting with a gynecological LPD. A literature review was also performed. Results: Of the 13 evaluated women, 9 had ovarian involvement, 3 had cervical involvement, and 1 had uterine involvement. The most common lesion characteristics were homogenous masses (11), with mild contrast enhancement (9), followed by soft-tissue necrosis (4), prominent blood vessels displaced by the lesions (4), linear arrangement of cysts at the periphery of the ovaries (3), and "touching" ovaries in all cases of bilateral ovarian involvement. Conclusions: A solid large homogeneous mass with mild contrast enhancement should alert the radiologist to the possibility of the differential diagnosis of LPD. Radiologists should be "the gatekeepers" by raising this possibility to avoid unnecessary surgery and enable appropriate treatment.